An analysis of the role of the Department of Water and Forestry in the management of the Xikundu Water Project in the Northern Region of the Limpopo Province of South Africa - Taunyane, Letlhogonolo Bridgitte (University of Limpopo (Turfloop Campus), 2007)
The aim of this inquiry was to analyze the role played by the Department of Water Affairs and Forestry in service delivery, i.e. supply water in the northern region of the Limpopo Province. Not much research has been conducted in this field especially in the Limpopo Province. Public Services are not a privilege in a civilized and democratic society, but are a legitimate expectation. Hence, meeting the basic needs of all citizens is one of the five key programmes of the government’s Reconstruction and Development Programme (RDP). From the literature review, it was evident that service delivery is essential in the communities, and, as such, government departments and municipalities have a critical role to play. The study also aimed to examine the problems and challenges the community faced during the construction of the community development programme. It reflected on the importance of consultation, project management and even feedback as a point of departure in showing both to the department and the municipality the attitudes and perceptions of communities and their level of satisfaction with regard to the effectiveness of service delivery. In order to achieve this goal, an interview was conducted with various interviewees. The participants ranged from the youth to the elderly citizens in the community, and the government officials. The main patterns that emerged from the collected data related to the dissatisfaction of the community about the lack of consultation. It would be advisable for government, especially municipalities, to take cognizance of the results and concerns in an effort to improve and ensure the effective service delivery as stipulated in the Reconstruction and Development Programme document.
Thesis (MPA.) --University of Limpopo, 2007
Keywords: Water supply; Community development; 553.70968; Water-supply, Rural; Water-supply, Rural - South Africa - Limpopo